Magnetic State of Multilayered Synthetic Antiferromagnets during Soliton Nucleation and Propagation for Vertical Data Transfer. Issue 15 (9th May 2016) - Fernández‐Pacheco, Amalio; Steinke, Nina‐Juliane; Mahendru, Dishant; Welbourne, Alexander; Mansell, Rhodri; Chin, Shin L.; Petit, Dorothée; Lee, JiHyun; Dalgliesh, Robert; Langridge, Sean; Cowburn, Russell P.
Abstract : Magnetic solitons in multilayered synthetic antiferromagnets (SAFs) have been recently proposed as data carriers for vertical data transfer, constituting a promising approach for 3D spintronic systems. Here, the nucleation and propagation of solitons in CoFeB/Ru SAFs are investigated under external magnetic fields by magnetooptical Kerr effect (MOKE), magnetoresistance (MR), and polarized neutron reflectivity (PNR) measurements. By comparing MOKE and MR measurements with macrospin simulations, the key steps of the mechanism behind soliton nucleation, triggered by the surface spin‐flop transition and involving the switching of several layers, are determined. PNR confirms this scenario, and proves the correct propagation of solitons, with their expulsion leading to data inversion (NOT gate functionality). Additionally, the structure of solitons after nucleation is determined, finding them to be achiral under external magnetic fields. Abstract : Probing the magnetic state of magnetic multilayer systems during vertical data transfer is very challenging compared to standard planar devices. Here, by using magnetoresistance measurements and polarized neutron reflectometry, the detailed spin configuration of such systems is determined, showing how small interfacial differences between magnetic layers affect their operation.